2010
DOI: 10.14310/horm.2002.1255
|View full text |Cite
|
Sign up to set email alerts
|

The differential impact of volatile and intravenous anaesthetics on stress response in the swine

Abstract: OBjEcTIVE: To compare the effects of various anaesthetics on stress response in the presence and absence of surgical stimulation. DESIGN: Twenty-nine pigs scheduled to undergo surgical central vein catheter placement were randomly allocated to receive only sedation with ketamine-midazolam (group SHAM, n=5) or general anaesthesia with either propofol 8 mg/kg/h (group PROP, n=8), sevoflurane 1.0 MAc (group SEVO, n=8) or desflurane 1.0 MAc (group DESF, n=8). Following surgery, anaesthesia was maintained for a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…1 We would like to highlight earlier human data of ours (some of which unpublished to date) as well as from others that are pertinent to this interesting line of research and generally supportive of the authors' conclusions.…”
Section: Dear Editorsupporting
confidence: 65%
“…1 We would like to highlight earlier human data of ours (some of which unpublished to date) as well as from others that are pertinent to this interesting line of research and generally supportive of the authors' conclusions.…”
Section: Dear Editorsupporting
confidence: 65%
“…It was previously demonstrated that inhalational anaesthetic agents do not affect the plasma levels of TSH (17,18). Nevertheless, an opposite result was obtained in our study: plasma TSH levels reached their peak levels at the first hour postoperatively in both Groups P and D. The answer may be hidden in the use of remifentanil infusion.…”
Section: Discussionmentioning
confidence: 99%
“…If not, general anaesthesia will have to be provided in hypo-or hyperthyroid states. Under these circumstances, it is obligatory to administer an appropriate anaesthetic agent that has minimal effects on thyroid hormone levels in order to protect the patient from unwanted side effects of thyroid disease (8). Many studies investigated the effects of the type of anaesthesia and anaesthetic agents on thyroid hormone levels, but few reports focused on the effects of desflurane on thyroid functions (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, only the distal portion of the trachea, the lining among the apical lobes of the lungs, and the area proximal to the primary bronchi were included in the quantification of radioactivity. Moreover, ketamine, although providing mild anesthesia with relatively normal breathing capability (43,44), causes an increased production of mucus and saliva (45,46), which may have promoted the mucociliary clearance of either the nanocomplexes or the Tc-99m RTNs from the trachea. Although atropine should counteract this effect (47), the amount used might not have been sufficient.…”
Section: Discussionmentioning
confidence: 99%